Analisis Pengaruh Marketing mix (4p) Terhadap Keputusan Pembelian Konsumen Kopi Sidikalang(Studi kasus Kopi Tanpak Sidikalang Kab.Dairi) - Amal, Utami Padang; Zainarti, Zainarti; Aisyah, Siti (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
Sidikalang is known as a producer of robusta coffee beans which are known to have high levels of caffeine, reaching 70-80%. The quality of the coffee beans produced has stronger physical and taste characteristics. This study aims to determine and analyze the influence of Marketing Mix(4p) on consumer purchasing decisions for Sidikalang Coffee (Case study of Sidikalang's Tapik Coffee). This type of research used is quantitative research. Data was collected using questionnaire data and direct surveys filled with 100 respondents. The analysis tools used are validity test, reliability test, classic assumption test, multiple linear regression, t test (partial) and f test (simultaneous). The results of the study concluded that the Product, Price and Promotion Variables had a significant effect on the purchasing decisions of Sidikalang's coffee consumers (partially). Location did not have a significant effect on the purchase decision. Sidikalang's appearance, which is so delicious, is no longer in doubt about its quality.